Corruption as a discrimination mechanism - Novoa Curich, Yvana Lucía (2016)
This research paper deals with the phenomenon of corruption as a crime not only from the perspective of criminal law, but as the cause of violations of fundamental rights. The article explains the concept of corruption and places this phenomenon in the international legal framework. Likewise, the content of the right to equality and the prohibition of discrimination is developed in this article. It exposed, with the help of examples, how that corruption violates Human Rights, affecting vulnerable groups in a particular and special way, and how well it ends up being a mechanism of structural discrimination in Peru.